Efektivitas Model Learning Cycle 7E Berbantuan Media Pop-Up Book Terhadap Pemahaman Konsep IPAS Siswa Kelas IV SD 4 Dersalam - Malichatuz Zahro Assaidah; Siti Masfuah; Ika Oktavianti (Mataram University, 2026)
This study was motivated by students’ low conceptual understanding in science education. The study aimed to examine the difference in mean pretest and posttest scores after implementing the 7E Learning Cycle model aided by a Pop-Up Book, as well as to determine the improvement in students’ conceptual understanding through the N-Gain test. The study employed a quantitative approach with a one-group pretest-posttest design. The study subjects consisted of 24 fourth-grade students at SD 4 Dersalam, selected using saturation sampling. Data were collected through tests, observations, and interviews, then analyzed using normality tests, the Paired Sample t-test, and the N-Gain test. The results showed that the 7E Learning Cycle model supported by Pop-Up Book media had a significant effect on students’ conceptual understanding of IPAS. The results indicated that students’ average scores increased from 60.9 on the pretest to 85.8 on the posttest. The N-Gain test result of 0.6461 falls into the moderate category with an effectiveness of 64.6% (moderately effective). These findings indicate that the 7E Learning Cycle model supported by Pop-Up Book media can serve as an alternative learning approach to enhance students’ understanding of IPAS concepts and support active, meaningful, and student-centered learning.